O significado do conceito conhecimento para pesquisadores que estudam gestão do conhecimento: uma análise a partir dos trabalhos publicados nos anais de eventos da ANPAD - Rodrigues, Marcos Mazurek (2012)
The objective of this study is to investigate the perception of the meaning of the concept knowledge for the researchers in the knowledge management area. A multidimensional analysis model was developed to analyze the way authors refer to the knowledge concept in their research. Proceedings of the Anpad meetings from 1997 to 2010 were used as the source of papers to be analyzed. The proposed model included the analysis of the main attributes and properties of knowledge, structured in three different dimensions: formal issues, describing the main research strategies, , semantic issues, with the investigation of the epistemological dimension of knowledge, and cognitive issues, in order to find out the relationship that exists between the area in which the researchers were educated, the academic community to which they belongs and their understanding of the concept knowledge. The theoretical framework that was used involved the discussion of different issues concerning knowledge, knowledge management and the creation of organizational knowledge, as well as the communication dimensions involved in building scientific knowledge. The methodology that was used involved categorical content analysis, which was performed in a quantitative, exploratory, descriptive but also qualitative inferential way involving papers about knowledge management published in the proceedings of Anpad meetings over the years. It was carried out in an attempt to identify differences in perceptions related to semantic issues. Results show that knowledge is perceived as tacit in some cases and explicit in others. It is usually considered capturable and disseminatable in the organization. Many times, researchers do not make clear distinction between knowledge and information, when discussing them in their papers. The area in which the researchers were educated, their academic communities as well as the cooperation networks they form influence their perception of the meaning of knowledge.